The role of Islamic banks In enhancing SMEs' access to financing via musharakah Financing - Abd Rahman, Nur Hasnida (IIUM Press, 2017)
Most Islamic banks’ operations are dominated by debt based financing, which limit SMEs' access to financing due to their inability to provide adequate collateral, oblige high-profit payment, and provide sufficient track records. In relation to this, many past studies have discussed that Musharakah financing would be functioning as a viable alternative financing for SMEs to overcome this problem. However, most of the Islamic banks are reluctant to operate Musharakah financing as it is vulnerable to agency problems which expose the banks to high financing risks. Moreover, SMEs' unwillingness to allow banks to take part in their business operations also impede the application of Musharaka financing. In view of this problem, this study is conducted to evaluate bank's participation in Musharakah financing with a view to determining its viability as an alternative financing for SMEs. Using survey questionnaire administered on SMEs in Malaysia, data elicited was subjected to statistical analysis using structural equation modeling. The results demonstrate SMEs' agreement on the bank's participation in their business operations thus indicating the potential of Musharakah as a viable financing for SMEs.